Effectiveness Of Manual Material Handling Tools For Chicken Feed Transporting Rails And Online Marketing Websites - Wahrini, Retyana (International Journal of Global Sustainable Research, 2024)
This research aims to solve problems in the process of feeding broiler chickens on increasing the skills of chicken farmers. The mentoring activities carried out include assisting chicken farmers in using production technology assistance and demonstrating if there is damage or errors in operating Manual Material Handling (MMH) tools or difficulties in managing the website. The results of this research are: 1) 90% respondents understand how to operate Manual Material Handling tools; 2) 90% respondents understand the components of Manual Material Handling; 3) 95% of respondents strongly agree with the material duration in operating manual material handling; 3) 95% participant evaluation results after participating in training for the category of using MMH to Help Broiler Chicken Production answered strongly agree.